The translator’s bookshelf: the role of reading in a freelance translator’s continuing professional development portfolio - Fulford, Heather (The Journal of Specialised Translation, 2012)
The role and place of reading in the development, maintenance and growth of a translator's knowledge and skills are discussed. Reading is highlighted as a valid, and indeed valuable, form of continuing professional development (CPD) activity for freelance translators. Consideration is given to the range of reading in which a translator can usefully engage for professional development purposes, the forms of learning that can occur through the reading of particular types of materials, and the approaches a translator can take to reading in order maximise the learning to be derived from it. The benefits and challenges are considered of including reading in a translator's programme of CPD activity. A typology of reading for professional development is outlined for freelance translators.